Credit Guarantee Corporation Malaysia Berhad (CGC): an overview / Anita Abu Hassan and Najah Mokhtar - Abu Hassan, Anita; Mokhtar, Najah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Credit Guarantee Corporation Malaysia Berhad (CGC) has existed in Malaysia’s financial system for half of a century. Forty-eight years to be exact. Monitored and supervised by the central bank of Malaysia known as Bank Negara Malaysia (BNM). CGC was established initially to support small businesses obtaining a credit facility, especially from the commercial bank by providing a loan guarantee. The loan guarantee is given to any eligible borrower in which the loan was packaged under specific CGC guarantee schemes by the participated financial institutions. Since the formation of the CGC, there are nearly fifty guarantee schemes have been introduced to the market. Some of the guarantee schemes have been discontinued over time and replaced by the new guarantee schemes which are more relevant to the need of the current market and the dynamic change of the Micro, Small, and Medium Enterprises (MSMEs). Currently, CGC offers eight guarantee schemes initiates by the financial institutions, four direct guarantee schemes which originated by CGC branches, and three government-backed guarantee schemes.